Validation and Cultural Adaptation of the Sinhala Translation of the Cardiff Acne Disability Index (CADI) - Liyanage A; Prathapan S; Jayarathne C; Ranaweera LS; Perera J (Patient Related Outcome Measures, 2024)
Achala Liyanage,1 Shamini Prathapan,2 Chathurika Jayarathne,3 Ludhmila Savani Ranaweera,3 Jennifer Perera4 1Senior Lecturer and Specialist Dermatologist, Department of Community Medicine, Faculty of Medicine, University of Ruhuna, Karapitiya, Sri Lanka; 2Professor, Department of Community Medicine, Faculty of Medical Sciences, University of Sri Jayewardanapura, Nugegoda, Sri Lanka; 3Pre-Intern Medical Officer, Department of Microbiology, Faculty of Medicine, University of Colombo, Colombo, Sri Lanka; 4Emeritus Professor, Faculty of Medicine, University of Colombo, Colombo, Sri LankaCorrespondence: Jennifer Perera, Email jenniferp@micro.cmb.ac.lkIntroduction: Quality of life (QoL) is impaired in patients with acne vulgaris. The Cardiff Acne Disability Index (CADI) that assesses QoL of acne patients was initially developed in English and is being currently used widely after being validated in different languages. This study was conducted to validate the CADI in Sinhala, a language used by the majority of Sri Lanka.Materials and Methods: The CADI was translated into Sinhala, and lingually validated as per published guidelines. This CADI-Sinhala version and the Sinhala version of the Dermatology Life Quality Index (DLQI) were simultaneously administered to 150 Sinhala-speaking young adults with acne. The clinical severity of acne was assessed using the Global Acne Grading System (GAGS). The Cronbach’s alpha and Spearman correlation coefficients were used to determine the internal consistency, reliability, and validity of the CADI-Sinhala. Construct validity was examined using a factor analysis.Results: The study included 90% females and their mean age was 23 (SD, 2.5) years. The majority (97.3%) had acne of mild to moderate severity when measured by the GAGS. The CADI-Sinhala Scale showed a Cronbach’s alpha coefficient of 0.819 indicating high internal consistency and reliability. The mean item-total correlation coefficient was 0.74 (range, 0.42– 0.87) with CADI Q3 having the lowest correlation. CADI Sinhala showed a strong and highly significant correlation with the Sinhala DLQI (Spearman’s rho = 0.66; P< 0.001) indicating concurrent validity. The correlation with GAGS was of low intensity, although it was statistically significant (p < 0.01).Conclusion: The CADI-Sinhala is a reliable and valid tool for assessing the QoL of Sinhala-speaking acne patients. This five-item tool will help clinicians to provide holistic treatment through improved understanding of patient’s perspectives.Keywords: acne vulgaris, Cardiff acne disability index-Sinhala, validation, quality of life